2012
DOI: 10.1080/13825585.2012.706247
|View full text |Cite
|
Sign up to set email alerts
|

Executive and memory correlates of age-related differences in wayfinding performances using a virtual reality application

Abstract: The aim of this study was to evaluate in large-scale spaces wayfinding and spatial learning difficulties for older adults in relation to the executive and memory decline associated with aging. We compared virtual reality (VR)-based wayfinding and spatial memory performances between young and older adults. Wayfinding and spatial memory performances were correlated with classical measures of executive and visuo-spatial memory functions, but also with self-reported estimates of wayfinding difficulties. We obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
39
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 50 publications
11
39
1
1
Order By: Relevance
“…Wayfinding is a process of determining and following a route or path from an origin to a destination and is an outcome of a collection of skills such as route memory, landmark use, and survey knowledge (Wiener, Büchner, & Hölscher, 2009). Correlational studies have shown that wayfinding performance is positively, albeit somewhat weakly, associated with spatial memory (Nori, Grandicelli, & Giusberti, 2009; Taillade et al, 2013), mental rotation (Kozhevnikov, Motes, Rasch, & Blajenkova, 2006; Malinowski, 2001), and closure (Hegarty, Montello, Richardson, Ishikawa, & Lovelace, 2006; Kirasic, 2000; Meneghetti, Fiore, Borella, & De Beni, 2011). On the other hand, wayfinding, as a task on geographic large-scale environment, is also unique in its own form and distinguished from the four spatial abilities as reviewed here, which are mostly measured by psychometric tasks (for a review and discussion, see Allen, 1999; but see Hegarty et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Wayfinding is a process of determining and following a route or path from an origin to a destination and is an outcome of a collection of skills such as route memory, landmark use, and survey knowledge (Wiener, Büchner, & Hölscher, 2009). Correlational studies have shown that wayfinding performance is positively, albeit somewhat weakly, associated with spatial memory (Nori, Grandicelli, & Giusberti, 2009; Taillade et al, 2013), mental rotation (Kozhevnikov, Motes, Rasch, & Blajenkova, 2006; Malinowski, 2001), and closure (Hegarty, Montello, Richardson, Ishikawa, & Lovelace, 2006; Kirasic, 2000; Meneghetti, Fiore, Borella, & De Beni, 2011). On the other hand, wayfinding, as a task on geographic large-scale environment, is also unique in its own form and distinguished from the four spatial abilities as reviewed here, which are mostly measured by psychometric tasks (for a review and discussion, see Allen, 1999; but see Hegarty et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Older adults have been shown to place priority on motor control during dual-task walking, so as to avoid falling but at the expense of walking speed (Hollman et al, 2007) or talking (for a review, see Beurskens and Bock, 2012;Sparrow et al, 2002). In this line, the greater declines of executive functions in mild cognitive impairment and Alzheimer's disease (da Costa et al, 2013) may be why these medical conditions are strongly associated with a higher risk of falling (Delbaere et al, 2012;Sheridan and Hausdorff, 2007), a higher risk of being injured during street crossing (Gorrie et al, 2008) and navigation difficulties in real-life or simulator studies (e.g., Kliegel et al, 2007;Salthouse and Siedlecki, 2007;Taillade et al, 2013).…”
Section: Impact Of Cognitive Changesmentioning
confidence: 88%
“…Interestingly, studies using transfer tasks reported an age-related effect on the wayfinding performances [21], [30], [31], but failed to find this effect on the spatial memory performances (route and survey knowledge measures) [21], [30]. Taillade et al [21] and Foreman et al [30] showed differences on wayfinding performances between younger and older adults but no difference for spatial memory tasks. Foreman et al [30] studied the transfer of spatial knowledge from a virtual shopping mall to its real version.…”
Section: Introductionmentioning
confidence: 99%
“…Wayfinding is classically described as a purposeful, directed, and motivated movement from an origin to a specific distant destination, which cannot be directly perceived by the traveler [19], [20] and is likely dependent on executive functioning, such as planning abilities and decision making [1], [21]. Indeed, prefrontal cortex activations are found in relation with goal proximity [22], or with the planning and monitoring processes during navigation [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation